The relationship between neutrophil lymphocyte ratio and 28-day mortality in intensive care patients - Yildiz, Hamit (Progress in Nutrition, 2019)
The aim of this study is to investigate the relationship between neutrophil to lymphocyte ratio (NLR) at admission to ICU and 28-day mortality in patients with sepsis and septic shock, which is an important cause of mortality in the intensive care unit (ICU). Data of consecutive 398 patients with sepsis and septic shock who interned to ICU were retrospectively reviewed and included in the study. NLR, 28-day mortality and other laboratory datas were collected retrospectively from the ICU archive. 111(27.89%) patients died within 28 days after admission to ICU. NLR was higher in patients with sepsis group (p:0.01). However, 28-day mortality was higher in septic shock group (p0.05). Patients with sepsis admited to ICU were found to have higher NLR at admission. This study supports that NLR at admission has no effect on 28-day mortality.